Hepatitis E seroprevalence, cases and management in a large German centre for liver transplantation - Nkongolo, Shirin; Mohr, Isabelle; Wenzel, Jürgen J.; Khalid, Dina; Mieth, Markus; Mehrabi, Arianeb; Weiss, Karl Heinz; Schnitzler, Paul (Liver cancer international, 2022)
Background and Aims Hepatitis E virus (HEV) is an increasingly recognised pathogen in industrialised countries, in particular genotype 3. Patients with underlying liver disease are at increased risk for severe course of the infection. Additionally, patients receiving immunosuppressive therapy can develop chronic HEV infection, which may cause further liver damage and ultimately lead to cirrhosis, decompensation or death. Methods This retrospective study assessed 1023 patients on the waiting list for liver transplantation, of which 636 were transplanted, for conducted HEV diagnostics, courses of disease and management, in the time from 2007 to 2018. Viral loads and HEV genotypes were determined retrospectively for selected cases. Results We found a seroprevalence of 29.7%. Forty-five patients (4.4%) seroconverted during the study period, indicating newly acquired infection. HEV replication was detected in nine patients (0.9%), seven of which were managed in our clinic and further analysed. Three of these patients were diagnosed with active HEV infection retrospectively. All patients with replicating HEV were liver-transplanted and therefore treated with immunosuppressants; four developed chronic infection >3 months. Two patients were also diagnosed with graft rejection when they had active hepatitis E. Patients who received antiviral treatment with Ribavirin cleared the infection and normalised alanine aminotransferase (ALT) levels within few weeks. Conclusion The results argue for more and systematic HEV testing of liver-transplanted patients, in routine settings and especially when ALT is elevated, as infections may be significantly underdiagnosed. Patients receiving immunosuppressive therapy who develop chronic infection can effectively be treated to prevent further liver damage.